FRI0464 Development of the Classification Criteria for GIANT Cell Arteritis in the Diagnostic and Classification Criteria for Vasculitis Study: A Pilot Study Using A Panel Review Methodology. (10th June 2014) - Ponte, C.; Grayson, P.C.; Suppiah, R.; Robson, J.; Anthea, C.; Judge, A.; Merkel, P.A.; Watts, R.A.; Luqmani, R.A.
Abstract : Background: The Diagnostic and Classification Criteria for Vasculitis (DCVAS) Study is a multinational observational study to develop diagnostic criteria and to update classification criteria for the primary systemic vasculitides. By 2015 we aim to include data from over 2000 vasculitis patients and 1500 comparators. For the development of the new Giant Cell Arteritis (GCA) classification criteria a combination of panel review and data-driven methods will be tested, comparing cases which have a submitted diagnosis of GCA with other forms of vasculitis. Objectives: To test the panel review methodology in the development of the GCA classification criteria. To measure the diagnostic agreement among the panel review, and with the submitting physician, for different groups of GCA patients and comparators. Methods: By April 2013, 1619 patients had been recruited; 821 had complete 6 month follow-up data. Sixty cases with a submitted diagnosis of GCA and forty cases with other forms of vasculitis as comparators (16 Takayasu arteritis, 4 Isolated aortitis, 14 Other Large-vessel vasculitis and 6 Primary CNS angiitis) were randomly extracted and developed into clinical vignettes (CV) which were assessed for diagnoses by 5 independent vasculitis experts using an online platform. For each answer a level of certainty was provided. Results: The 100 CV (67 women, 33 men) had a mean age of 63.9±16.3 years (range 21-86). The panel review agreed with the submitted diagnosis of each vasculitis sub-type in 79% of all the cases (91% agreement for GCA, 62% for comparators) with an intraclass correlation coefficient of 0.89 (CI 0.86-0.93). The panel review classified 27% of the comparators as having GCA. Temporal artery biopsy (TAB) was performed in 54 submitted GCA cases where 38 demonstrated vasculitis. For the biopsy positive cases the review panel agreed with the diagnosis of GCA in 98% (level of certainty: definite 93%, probable 5% and possible 3%). In the submitted GCA cases where the TAB was non-diagnostic (16) or not performed (6) the panel review agreed with this diagnosis in 81% (level of certainty: definite 9%, probable 48%, possible 40% and unlikely 3%). There were clinical differences between patients with a diagnostic and non-diagnostic TAB: Differences regarding the prevalence of headache and visual symptoms were also found in patients with or without large-vessel involvement (67% and 78% vs 50% and 33% [p 0.52; p 0.05]). Conclusions: The panel review disagreed with the submitting physician diagnosis of GCA in 9% of the cases. This disagreement was significantly reduced in cases with positive TAB (where the prevalence of typical GCA symptoms was higher). This exercise explores the possibility of using TAB positive cases as gold standard to derive GCA classification criteria and highlights the challenge of defining a gold standard in cases of large vessel vasculitis without biopsy confirmation of disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2717